Trafficking human beings and organized crime - Kastrati, Shqipe (Technium Social Sciences Journal, 2022)
According to the United Nations Protocol, Trafficking in Human Beings (HRT) means: "The recruitment, transportation, transfer, concealment or taking of persons for any purpose or in any form by threat or use of force or by abduction, deception, cunning, coercion or abuse of power in order to slavery, forced labor, and slavery". Trafficking is a global problem. Based on the statistics of different world organizations, every year around 2,000,000 men, women and children are trafficked, with 80% of them being women and girls, while about 50% are juveniles. Trafficking in human beings, after trafficking in narcotic drugs and weapons, is considered to be the most widespread criminal activity in the world. Looking at the monetary aspect the figures are astronomical. The United Nations Center for Crime Prevention estimates that the global profit from this type of crime is over 8 billion. The International Convention of 2000, with the term "Organized Criminal Group" means a structured group of consisting of three or more persons who exist for a certain period of time and who cooperates in order to commit one or more serious crimes or offenses established by this Convention with a view to obtaining direct or indirect benefits property or financial. What is most tempting for "organized crime" is the exploitation of markets where there is a high demand for certain services and goods, which, because of the restrictive laws and regulations currently in that country, can not to be filled in legally. Factors that promote organized crime are factors of political, social and economic character. These various factors and circumstances have influenced the emergence of early forms of illicit organized activities as well as the evolution and sophistication to the present day.